Identifying cost‐effective recovery actions for a critically endangered species. Issue 1 (18th November 2021) - Pritchard, Rachel A.; Kelly, Ella L.; Biggs, James R.; Everaardt, Annika N.; Loyn, Richard; Magrath, Michael J. L.; Menkhorst, Peter; Hogg, Carolyn J.; Geary, William L.
Abstract: Threatened species managers are often required to make swift decisions in the face of considerable uncertainty. We tested a structured approach for evaluating conservation options for the critically endangered orange‐bellied parrot. The Orange‐bellied Parrot Recovery Team provides advice to government agencies to inform the allocation of a limited number of captive‐bred birds to different release scenarios. Using a structured expert elicitation approach, we determined that scenarios where more fledglings were released were more cost‐effective compared to other options. Following this finding in 2019, the recovery team adjusted plans and allocated additional birds to fledgling release, a response that contributed to an increase in wild birds migrating in 2020 and 2021. The challenges facing orange‐bellied parrot conservation, including limitations in animals, time and resources, and high uncertainty, are common for threatened species recovery programs. Here we show that a structured process can help managers grapple with these complex trade‐offs to make timely decisions. Abstract : A structured approach for evaluating conservation options for the critically endangered orange‐bellied parrot. Management scenarios where more fledglings were released were more cost‐effective compared to other options, which once implimented contributed to an increase in wild birds migrating in 2020. Here is a juvenile release orange‐bellied parrot photographed on in mainland Australia after successful migration in 2020 Credit: Brian Aherne.